IoT Oxymeter Starter Prototype As An Employee Health Monitoring Tool In The Blynk Integrated Palm Industry - Muhammad Akbar Syahbana Pane; Rahmad Dian; Ratu Mutiara Siregar; Balqis Nurmauli Damanik; Asnita Yani; Alisarjuni Padang; Khairul Saleh (University of Science and Computer Technology, 2024)
One of the main challenges faced by workers in the palm oil industry is routine health monitoring. Therefore, innovation is needed in the form of health monitoring tools that can facilitate and increase the efficiency of employee health monitoring. The Internet of Things (IoT) has become an increasingly popular solution to overcome these challenges. The use of this technology is expected to increase employee health resilience, detect potential health problems early, and provide a quick response to health conditions that require medical attention.